Entrepreneurship Capability by Triple Series Innovations in Building Competitive Resilience within the Airline Industry - Sukardi, Samudra; Wahyuni, Sari; Rachmawati, Riani (Aptisi Transactions On Technopreneurship (ATT), 2025)
This research examines how entrepreneurship capability affects competitive resilience within the airline business, focusing on innovation sequences along the value chain as a solution to environmental turbulence. The study aims to investigate the mechanism through which entrepreneurship capability contributes to resilience by mediating organizational, digital, and business model innovations. The study involved 250 CEOs and top leaders in Indonesian airlines. Data were collected via surveys and analyzed using SPSS 25 and Smart Partial Least Squares (SmartPLS) 4. Findings show that entrepreneurship capability does not directly affect digital collaboration or business model innovation. Its effect occurs indirectly through organizational innovation, which promotes digital distribution innovation, leading to business model innovation. Together, these innovations strengthen resilience in turbulent environments. The study highlights the critical role of the triple serial relationship among organizational innovation, digital distribution, and business model innovation in navigating crises such as the COVID-19 pandemic. Practically, airline leaders should use entrepreneurship capability to drive innovation, support digital transformation, and adopt customer focused strategies to sustain competitiveness. This research contributes original insight by revealing how entrepreneurship capability indirectly fosters resilience through innovation sequences, aiding airlines in adapting to market changes. The study aligns with SDGs 8 (Decent Work and Economic Growth) by promoting entrepreneurship led growth and SDGs 9 (Industry, Innovation, and Infrastructure) through advancing innovative and resilient business practices.